Adverse Left Ventricular Remodeling and Age Assessed with Cardiac MR Imaging: The Multi-Ethnic Study of Atherosclerosis - Eng, John (Radiology, 2016)
PURPOSE: To evaluate age-related left ventricular (LV) remodeling during longitudinal observation of a large cohort of asymptomatic individuals who were free of clinical cardiovascular disease at baseline. MATERIALS AND METHODS: The applicable institutional review boards approved this study, and all participants gave informed consent. Cardiac magnetic resonance (MR) imaging was used to identify longitudinal changes in LV structure and function in 2935 participants who underwent baseline and follow-up cardiac MR imaging in the Multi-Ethnic Study of Atherosclerosis. Participants were free of clinical cardiovascular disease at baseline. Participants who experienced an incident coronary heart disease event were excluded. Data were analyzed with multivariable mixed-effects regression models in which the outcome was cardiac MR imaging measurement, and the covariates included follow-up time and cardiac risk factors. RESULTS: Participants were aged 54–94 years at follow-up, and 53% of the participants were women. Median time between baseline and follow-up cardiac MR imaging was 9.4 years. Over this period, LV mass increased in men and decreased slightly in women (8.0 and −1.6 g per decade, respectively; P < .001). In both men and women, LV end-diastolic volume decreased (−9.8 and −13.3 mL per decade, respectively; P < .001), stroke volume decreased (−8.8 and −8.6 mL per decade, respectively; P < .001), and mass-to-volume ratio increased (0.14 and 0.11 g/mL per decade, respectively; P < .001). Change in LV mass was positively associated with systolic blood pressure and body mass index and negatively associated with treated hypertension and high-density lipoprotein cholesterol level. In men, the longitudinal LV mass increase was in contrast to a cross-sectional pattern of LV mass decrease. CONCLUSION: As patients age, the LV responds differently in its mass and volume between men and women, although both men and women experience increased concentric LV remodeling with age. In men, the opposition of longitudinal and cross-sectional changes in LV mass highlights the importance of longitudinal study. (©) RSNA, 2015 Online supplemental material is available for this article.